2019
DOI: 10.22219/jpbi.v5i3.9817
|View full text |Cite
|
Sign up to set email alerts
|

The effect of problem-based learning and naturalist intelligence on students' understanding of environmental conservation

Abstract: Environmental conservation understanding is one of the crucial factors which determines student attitudes and behavior towards the environment. This study aimed to investigate the effects of problem-based learning and naturalist intelligence on the students' understanding of environmental conservation. This experimental research was conducted at Madrasah Aliyah Negeri (MAN) 1 Praya which employed factorial design. The first factor was the levels of naturalist intelligence (high and low) and the second factor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
5
1
Order By: Relevance
“…They also maintain that ambient intelligence has a strong relationship with the environmental behavior of students because this intelligence enhances the ability to understand natural conditions. However, these results are different from those of Suhirman and Yusuf (2019), as they indicated that ambient intelligence had no significant relationship with the environmental behavior of university students. Verifying this relationship may be due to using a robust structural model considering all the antecedents of environmental behavior.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…They also maintain that ambient intelligence has a strong relationship with the environmental behavior of students because this intelligence enhances the ability to understand natural conditions. However, these results are different from those of Suhirman and Yusuf (2019), as they indicated that ambient intelligence had no significant relationship with the environmental behavior of university students. Verifying this relationship may be due to using a robust structural model considering all the antecedents of environmental behavior.…”
Section: Resultscontrasting
confidence: 84%
“…However, this relationship is still controversial in the literature. For example, Suhirman and Yusuf (2019) indicated that environmental intelligence did not have a direct relationship with the environmental behavior of university students.…”
Section: Environmental Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Students' ability to find and solve problems is influenced by their thinking ability (Zubaidah, 2018). Thinking ability is a process by which students develop ideas, finding knowledge, and solving the problems in their lives (Irwansyah & Lubis, 2016;Suhirman & Yusuf, 2019). Concerning science learning, students need thinking skills to understand the problems encountered in the environment, understand the processes that occur, and try to solve problems that arise.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of various models of learning that enhance students' logical thinking skills and learning outcomes can be an alternative. Based on the previous study, the learning models that are reported can play this aim are Guided Inquiry Learning (Artayasa et al, 2017;Dewi et al, 2013;and Zubaidah et al, 2017), Discovery Learning (Nuroso et al, 2016), Problem-Based Learning ( Suhirman & Yusuf, 2019;Sulastri et al, 2015), Direct Instruction (Sidik NH. & Winata, 2016), and Active Learning (Maisaroh & Rostrieningsih, 2010) The inquiry learning model is a model of learning that accommodates the essence of natural science as knowledge and process.…”
Section: Introductionmentioning
confidence: 99%